THU0136 NESFATIN-1 expression is associated with reduced atherosclerotic disease risk in patients with rheumatoid arthritis. (15th June 2017) - Robinson, C; Tsang, L; Solomon, A; Woodiwiss, A; Gunter, S; Hsu, H-C; Norton, G; Millen, A; Dessein, P
Abstract : Background: Nesfatin-1 comprises a peptide that is involved in appetite suppression, energy homeostasis and fluid regulation, and was recently documented to participate in a range of cardiometabolic pathways (1, 2). There is currently a need for the identification of novel biomarkers in the elucidation of CVD risk and its stratification in persons with rheumatoid arthritis (RA). The role of nesfatin-1 in cardiovascular disease risk among RA patients is uncertain. Objectives: We investigated the potential impact of nesfatin-1 on subclinical cardiovascular disease manifestations in patients with RA by determining the associations of nesfatin-1 concentrations with atherosclerosis and circulating levels of matrix metalloproteinase (MMP)-2 that mediates plaque stability and those of MMP-3 and MMP-9 that cause plaque vulnerability. Methods: Nesfatin-1 concentrations were measured in 236 (114 black; 122 white) RA patients. Relationships of nesfatin-1 concentrations with ultrasound determined carotid intima-media thickness (cIMT) and plaque and MMP levels were identified in confounder adjusted multivariate regression models. Results: Nesfatin-1 concentrations were inversely associated with c-IMT (β (SE) = -0.022 (0.008), p=0.00) and directly with MMP-2 levels (β (SE) =0.117 (0.031), p=0.00). After adjustment for conventional risk factors and RA characteristics, these associations persisted (c-IMT: β (SE) = -0.017 (0.008), p=0.04; MMP-2: β (SE) =0.116 (0.033), p=0.00). Patient characteristics did not influence the nesfatin-1-to-cIMT relation (interaction p≥0.7). By contrast, the Disease Activity Score in 28 joints (DAS28) and Clinical Disease Activity Index impacted the nesfatin-1-to-cIMT association (interaction p=0.04 and 0.02, respectively). Nevertheless, in stratified analysis, nesfatin-1 concentrations were related to those of MMP-2 in patients with no or mild (β (SE) =0.148 (0.054), p=0.00) and moderate or high disease activity (β (SE) =0.086 (0.041), p=0.04) as determined by DAS28 (cut-off value 3.6) as well as by CDAI (cut-off value =10) (β (SE) =0.130 (0.048), p=0.00 and 0.107 (0.046), p=0.02), respectively). Conclusions: Nesfatin-1 concentrations are consistently associated with a reduced atherosclerosis burden and increased MMP-2 levels in patients with RA. References: Oh-I S, Shimizu H. Identification of nesfatin-1 as a satiety molecule in the hypothalamus. Nature. 2006;443:709–712. Dore R, Levata L, Lehnert H, Schulz C. Nesfatin-1: functions and physiology of a novel regulatory peptide. Journal of Endocrinology. 2016; e-pub ahead of print: doi: 10.1530/JOE-16–0361. Disclosure of Interest: None declared